Palestine in the Second World War : Strategic Plans and Political Dilemmas. - Sharfman, Daphna (Sussex Academic Press, 2014)
While the conflicts and national aspirations in British mandatory Palestine in particular and the Middle East in general were evident before the outbreak of the Second World War, the war itself accelerated and enhanced national expectations and presented continuing tactical and strategic dilemmas to British, Arab, and Jewish leaders. British strategic policy during the war failed to provide answers to the political issues of the growing national demands in Palestine, and led to severe distrust of British policy among Arabs and Jews, as the two communities were framing mostly opposing reactions.